Calcium And Zinc Deficiency In Preeclamptic Women - Akhtar, Selina; Begum, Shelina; Ferdousi, Sultana (Journal of Bangladesh Society of Physiologist, 2012)
Background: Pre-eclampsia is the most common medical complication of pregnancy associated with increased maternal and infant mortality and morbidity. Reduced serum calcium and zinc levels are found associated with elevated blood pressure in preeclampsia. Objective: To observe serum calcium and zinc levels in preeclamptic women. Methods: This cross sectional study was carried out in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University, Shahbag, Dhaka between July 2009 to June 2010. In this study, 60 pregnant women of preeclampsia, aged 18-39 years with gestational period more than 20th weeks were included as the study (group B). For comparison age and gestational period matched 30 normotensive pregnant women control (group A) were also studied. All the subjects were selected from Obstetric and Gynae In and Out patient Department of BSMMU and Dhaka Medical College Hospital. Serum calcium was measured by Colorimetric method and serum zinc was measured by Spectrophotometric method. Data were analysed by independent sample t test and Pearson’s correlation coefficient test. Results: Mean serum calcium and zinc levels were significantly (p<0.001) lower in study group than those of control group. Again, serum calcium and zinc showed significant negative correlation with SBP and DBP in preeclamptic women. Conclusion: This study concludes that serum calcium and zinc deficiency may be one of the risk factor of preeclampsia. Therefore, early detection and supplementation to treat this deficiency may reduce the incidence of preeclampsia. DOI: http://dx.doi.org/10.3329/jbsp.v6i2.9758 JBSP 2011 6(2): 94-99